Intrathoracic Carcinoids: A 7-Year Tertiary Care Level Experience - NAUMAN TARIF, KAMRAN KHALID CHIMA, MUHAMMAD SHOAIB NABI, TALAT WASEEM (Journal of Fatima Jinnah Medical University, 2018)
Intrathoracic carcinoids are relatively uncommon chest cavity tumors. Timely diagnosis and the management of intrathoracic carcinoids have remained suboptimal in our deprived setup. Here we present our 7-year tertiary level experience dealing with this pathology. Materials & Methods: A total of 14 patients with intrathoracic carcinoids were diagnosed, adequately treated and prospectively followed up. The data were collected related to patient’s clinical presentation and management. Results: The mean age of the patients was 36.3 (28-53) years. Presenting features included cough (7/14), hemoptysis (8/14), pneumonia (4/14), pleurtic chest pain (3/14) and superior vena caval obstruction (1/14). CT scan, bronchoscopy and biopsy were employed for the diagnosis. 7 tumors were located in the right lung, 6 lesions were on the left side, while one lesion was located in mediastinum. None of the patients exhibited features of serotonin excess. All of the patients were mistreated as a case of tuberculosis at some time point during their illness. All of the patients were successfully managed by surgical intervention. One patient had serotonin excess crisis peroperatively, which was successfully managed with octreotide infusion and volume expansion. Two mortalities in this series were related to distant metastasis and concomitant hepatitis C related cirrhosis. Conclusions: Intrathoracic carcinoids still remain an under diagnosed and mistreated pathology in our setup. The detailed knowledge about this pathology and way to deal with it, is pre-requisite for its timely diagnosis and adequate management.